Regulation of the thrombin/protease-activated receptor 1 axis by chemokine (CXC motif) receptor 4 - Gao, Xianlong (J Biol Chem, 2020)
The chemokine receptor CXCR4, a G protein–coupled receptor (GPCR) capable of heteromerizing with other GPCRs, is involved in many processes, including immune responses, hematopoiesis, and organogenesis. Evidence suggests that CXCR4 activation reduces thrombin/protease-activated receptor 1 (PAR1)-induced impairment of endothelial barrier function. However, the mechanisms underlying cross-talk between CXCR4 and PAR1 are not well-understood. Using intermolecular bioluminescence resonance energy transfer and proximity ligation assays, we found that CXCR4 heteromerizes with PAR1 in the HEK293T expression system and in human primary pulmonary endothelial cells (hPPECs). A peptide analog of transmembrane domain 2 (TM2) of CXCR4 interfered with PAR1:CXCR4 heteromerization. In HTLA cells, the presence of CXCR4 reduced the efficacy of thrombin to induce β-arrestin-2 recruitment to recombinant PAR1 and enhanced thrombin-induced Ca(2+) mobilization. Whereas thrombin-induced extracellular signal-regulated protein kinase 1/2 (ERK1/2) phosphorylation occurred more transiently in the presence of CXCR4, peak ERK1/2 phosphorylation was increased when compared with HTLA cells expressing PAR1 alone. CXCR4-associated effects on thrombin-induced β-arrestin-2 recruitment to and signaling of PAR1 could be reversed by TM2. In hPPECs, TM2 inhibited thrombin-induced ERK1/2 phosphorylation and activation of Ras homolog gene family member A. CXCR4 siRNA knockdown inhibited thrombin-induced ERK1/2 phosphorylation. Whereas thrombin stimulation reduced surface expression of PAR1, CXCR4, and PAR1:CXCR4 heteromers, chemokine (CXC motif) ligand 12 stimulation reduced surface expression of CXCR4 and PAR1:CXCR4 heteromers, but not of PAR1. Finally, TM2 dose-dependently inhibited thrombin-induced impairment of hPPEC monolayer permeability. Our findings suggest that CXCR4:PAR1 heteromerization enhances thrombin-induced G protein signaling of PAR1 and PAR1-mediated endothelial barrier disruption.